Управління якістю підготовки з іноземної мови учнів загальноосвітньої школи - Мізерна, Тетяна Петрівна (НТУ "ХПI", 2011)
This article is devoted to the problem of quality management of pupils` schooling in foreign language in school of general education. Different approaches to the problem of quality management are analyzed. Quality management of pupils` schooling in foreign language is determined as a process of planning, achievements and improvements of quality characteristics.
Keywords: модернізація освіти; управління якістю; дослідження